Carbon and nitrogen pools in thermokarst-affected permafrost landscapes in Arctic Siberia - Fuchs, Matthias (Dr.); Grosse, Guido (Prof. Dr.); Strauss, Jens; Günther, Frank (Dr.); Grigoriev, Mikhail N.; Maximov, Georgy M.; Hugelius, Gustaf (2019)
Ice-rich yedoma-dominated landscapes store con- siderable amounts of organic carbon (C) and nitrogen (N) and are vulnerable to degradation under climate warming. We investigate the C and N pools in two thermokarst-affected yedoma landscapes – on Sobo-Sise Island and on Bykovsky Peninsula in the north of eastern Siberia. Soil cores up to 3 m depth were collected along geomorphic gradients and anal- ysed for organic C and N contents. A high vertical sampling density in the profiles allowed the calculation of C and N stocks for short soil column intervals and enhanced under- standing of within-core parameter variability. Profile-level C and N stocks were scaled to the landscape level based on landform classifications from 5 m resolution, multispectral RapidEye satellite imagery. Mean landscape C and N storage in the first metre of soil for Sobo-Sise Island is estimated to be 20.2 kg C m −2 and 1.8 kg N m −2 and for Bykovsky Penin- sula 25.9 kg C m −2 and 2.2 kg N m −2 . Radiocarbon dating demonstrates the Holocene age of thermokarst basin de- posits but also suggests the presence of thick Holocene- age cover layers which can reach up to 2 m on top of in- tact yedoma landforms. Reconstructed sedimentation rates of 0.10–0.57 mm yr −1 suggest sustained mineral soil accu- mulation across all investigated landforms. Both yedoma and thermokarst landforms are characterized by limited accumu- lation of organic soil layers (peat). We further estimate that an active layer deepening of about 100 cm will increase organic C availability in a sea- sonally thawed state in the two study areas by ∼ 5.8 Tg (13.2 kg C m −2 ). Our study demonstrates the importance of increasing the number of C and N storage inventories in ice- rich yedoma and thermokarst environments in order to ac- count for high variability of permafrost and thermokarst en- vironments in pan-permafrost soil C and N pool estimates.